2010
DOI: 10.1007/s11999-009-0880-0
|View full text |Cite
|
Sign up to set email alerts
|

Q-angle and J-sign: Indicative of Maltracking Subgroups in Patellofemoral Pain

Abstract: Mechanical factors related to patellofemoral pain syndrome and maltracking are poorly understood. Clinically, the Q-angle, J-sign, and lateral hypermobility commonly are used to evaluate patellar maltracking. However, these measures have yet to be correlated to specific three-dimensional patellofemoral displacements and rotations. Thus, we tested the hypotheses that increased Q-angle, lateral hypermobility, and J-sign correlate with three-dimensional patellofemoral displacements and rotations. We also determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
1
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 41 publications
(72 reference statements)
2
103
1
7
Order By: Relevance
“…These findings from our results may partially suggest a plausible explanation on the causes creating controversies among the studies over the Q-angle and PFPS (Freedman et al, 2014;Park & Stefanyshyn, 2011;Sheehan et al, 2010).…”
Section: Discussionsupporting
confidence: 50%
“…These findings from our results may partially suggest a plausible explanation on the causes creating controversies among the studies over the Q-angle and PFPS (Freedman et al, 2014;Park & Stefanyshyn, 2011;Sheehan et al, 2010).…”
Section: Discussionsupporting
confidence: 50%
“…To the best of our efforts, we have not been able to detect a comparable study to analogize. If the TTTG distance were indeed a radiological analogue of the Q-angle, which in itself is dubious, we could draw a parallel with the study by Sheehan et al [18] who found no correlation of the Qangle and the clinical J-sign. McDermott et al [19] deemed the J-sign useful as preoperative estimation of the distance needed for tibial tuberosity transfer, quantifying the clinical J-sign with the help of preoperative axial MRI-images in full knee extension and 30 degrees of flexion.…”
Section: Resultsmentioning
confidence: 62%
“…However, pain retro patella and the lateral face can also be diagnosed (4). These symptoms are caused by structural orbiomechani cal changes of the joint, which becomes exacerbated by activities such as going up and down stairs, sit for a prolonged period, squatting or kneeling (2,5,21), resulting in increased compressive forces in the joint patellofemoral (4,6). Other signs are also present as the patellar crepitus, swelling, and joint blockage (6).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism may be multifaceted (22,23). However, it may be related to abnormal biomecha nics, highlighting, among these, the static and dynamic unbalance (1,21).…”
Section: Introductionmentioning
confidence: 99%